Analysis of oil palm leaf phyllotaxis towards development of models to determine the fresh fruit bunch (FFB) maturity stages, yield and site-specific harvesting - Mustafa Albakri, Zulfadhli; Mohd Kassim, Muhamad Saufi; Abdullah, Ahmad Fikri; Harith, Hazreen Haizi (Universiti Putra Malaysia Press, 2019)
In order to ensure the optimum quality of palm oil, oil palm fruit needs to be harvested at the optimum maturity to avoid free fatty acid (FFA) accumulation. The high content of FFA not only reduces the quality of palm oil but also increases the refining cost. Optimum maturity based on plantation standard operating procedure (SOP) is determined by identifying the tree with loose fruit on the ground. The matured bunch is further identified based on the colour of the bunch. This paper presents a research work on formulation and validation of mathematical equations to estimate the maturity stages (age in weeks) of fresh fruit bunch (FFB) based on FFB position in oil palm phyllotaxis (spiral leaves arrangement) as an additional feature to confirm the maturity level of oil palm FFB. Regression analysis showed that the proposed method was able to estimate the maturity stages of oil palm FFB with the coefficient of determination R2 = 0.9 and a root mean square error (RMSE) of 1.58 weeks. The FFB yield estimation model and harvesting can be created based on the extracted data using the formula which will help in the planning of harvesting operation. Plantation manager can use this information to generate yield variability map and estimate the appropriate number of workers and machine. Planned harvesting operation can save a significant amount of time in site harvesting operation.